Novel biofuels derived from waste tyres and their effects on reducing oxides of nitrogen and particulate matter emissions. (1st January 2020) - Hossain, Farhad M.; Nabi, Md Nurun; Rainey, Thomas J.; Bodisco, Timothy; Bayley, Trevor; Randall, Denis; Ristovski, Zoran; Brown, Richard J.
Abstract: There are tons of waste tyres produced each year globally. Production of oil from the waste tyre not only manages the wastes but also produces fuels for compression ignition engines. In this investigation, a novel approach developed by Green Distillation Technologies in Australia was used to convert whole end of life tyres (ELTs) into carbon, steel, and tyre oil. The physicochemical properties of the tyre oil are similar to diesel fuel, and the fuel is miscible with diesel in any blended ratio. An engine experiment was conducted on a EURO IIIA diesel engine. All experiments were performed at constant speed and four different engine loads. Two blends (10% and 20%) of tyre oil were compared to reference diesel fuel. Exhaust emissions, including gaseous emissions, particulate matter (PM) and particulate number (PN) were investigated. The results indicate simultaneous reductions in both diesel PM and nitrogen oxides (NOx ) emissions with the tyre oil blends when compared to diesel. NOx emissions were reduced by approximately 30% with both blends with respect to diesel. The reduction in PM and PN emissions were in the range of 35–60% and 5–20%, respectively. Carbon monoxide (CO) were increased by ∼ 10% compared to the reference diesel except at quarter load. Insignificant change in brake power (BP), brake mean effective pressure (BMEP) and brake thermal efficiency (BTE) were observe with the tyre oil blends. The engine remained compliant with its EURO IIIA guidelines during the use of the tyre oil blends. Based on the engine performance and emission result, the tyre oil could be alternative to traditional diesel fuel. Highlights: Engine performance and emissions of diesel and two novel tyre oil blends are compared. Oxides of nitrogen were reduced by up to 30% with waste tyre oil blends. Particle mass and number emissions were reduced by 30% and 20%, respectively. The CO emissions were increased by 10% for the waste tyre oil blends.